Peran Guru dalam Membentuk Karakter Siswa Berbasis Ajaran Islam - Iskandar, Rudi; Apipudin (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
This research examines the role of teachers in shaping students' character based on Islamic teachings through a literature review. This abstract summarizes the key findings found from related literature and discusses how the concept of monotheism, teacher example, interpersonal interaction, and the application of the values ​​of justice and compassion are crucial factors in shaping student character. This study highlights the significance of teacher-student interaction in creating an Islamic educational environment that supports the formation of positive character. The results can become a basis for teachers and educational practitioners to implement effective strategies in shaping student character based on Islamic teachings.